The Matters in Teaching Reading Comprehension to EFL Students - Yuliana Natsir; Anisati Anisati (Studies in English Language and Education, 2016)
The purpose of this study was to find out the efforts that were being made by certified English teachers in teaching reading since reading is considered as one of the determiners of academic success. Descriptive qualitative research was used in this study; the subjects were two English teachers in Banda Aceh and the instrument was an interview guide. The interview questions were adapted from Fletcher, et al. (2012) that focused on curriculum, teacher preparation, teaching methodology, teaching instructions, authentic teaching materials, teachers’ perceptions toward reading attitudes of learners, barriers in teaching reading, and teaching strategies for helping ineffective readers. The interviews revealed that the efforts made by the teachers played a pivotal role at assisting students to achieve reading competency. The attitude of students toward reading was also important in the teaching-learning process. The strategies of the teachers towards the students who were not reading effectively were not in line with the strategies as suggested by some experts:  that the teacher should teach the students the strategies of how to read with interest, how to predict meanings, how to develop knowledge about the topic and so forth .These strategies were not implemented due to the situation and condition of the teaching environment. In brief, proper efforts by teachers to improve the learning environment could assist students to achieve better reading competency.